Rancang Bangun Sistem Informasi Geografis Menggunakan Framework 7 Dan Mapbox: Studi Kasus Wisata Jombang - Hardiyanto, Afri Fauzi; Airlangga, Primaadi (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2021)
There is a lot of mapping data scattered on the website of the geographic information system where the information needs to be displayed in order to be seen by the public. But the platform to display such data or information is still very limited, so it is necessary to create a mobile-based platform that is easily accessible to the public. This platform is expected to be able to display mapping results freely and can be made by various circles both academics and the general public. The platform that displays this mapping information using framework 7 and Mapbox with grapple research method (requirement gathering, analysis, design, development, deployment) with case study in this study is Jombang city tour, where will be done mapping tourist attractions according to the location.